Economic transnationalism and migration : Portuguese - American entrepreneurship and Portugal - Marçalo, Carolina (2022)
The main objective of this paper is to analyze economic aspects of transnationalism, particularly transnational entrepreneurship, in Portuguese-American communities—located in Massachusetts, Rhode Island, and New Jersey. Questions addressed in this study include the types of trade and investment that have developed under the frame of transnational ethnic businesses; the ties of Portuguese-American business owners to the ethnic market; and, alternatively, the expansion of businesses beyond the ethnic group. In addition, we also examine changes in business orientation from first to second and subsequent generations. We employ a predominantly qualitative methodology, including interviews and case studies. The main conclusions are that a) the ethnic characteristics of Portuguese-Americans are related to business development in the community and, particularly, to the creation of transnational ethnic businesses; b) the transition from the ethnic market to the mainstream American market and those of other ethnic groups is a condition for business growth; c) second and subsequent generations are associated with business modernization; and d) businesses can be oriented to both the mainstream and ethnic markets simultaneously.